2013
DOI: 10.1088/0953-2048/26/10/105022
|View full text |Cite
|
Sign up to set email alerts
|

High temperature heat treatment on boron precursor and PIT process optimization to improve theJcperformance of MgB2-based conductors

Abstract: Abstract:Promising results reported in our previous works led us to think that boron's production process plays a crucial role in MgBB 2 synthesis. A new method for boron preparation has been developed in our laboratory. This particular process is based on magnesiothermic reaction (Moissan's process) with the addition of an initial step that gives boron powder with nano-metric grain size. In this paper we report our efforts regarding optimization of PIT method for these nanometric powders and the resolution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In general the control of particles grain size and morphology is of crucial importance, especially from the industrial point of view. In fact varying the particles volume from the micrometric to nanometric scale a consequent change in physical properties arise [4]. As consequence of that many performances related grains of engineering materials critically depend on the scale and the morphology of the constituent particles.…”
Section: Introductionmentioning
confidence: 99%
“…In general the control of particles grain size and morphology is of crucial importance, especially from the industrial point of view. In fact varying the particles volume from the micrometric to nanometric scale a consequent change in physical properties arise [4]. As consequence of that many performances related grains of engineering materials critically depend on the scale and the morphology of the constituent particles.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary optimization has been possible on the LB0 powder (optimized LB0), which was produced in a sufficient amount (100 g) to allow a further heat treatment on the B, as reported in [13,21]. Regarding the C-doped powders, their amount was not sufficient to optimize them using the same process as explained in [13,25], because their synthesis was antecedent to LB0 optimization. Therefore, figure 8 shows that the optimized LB0 leads to have the best J c behavior for a wire.…”
Section: Resultsmentioning
confidence: 99%
“…Following the new boron synthesis process is possible to obtain a suitable precursor for MgB 2 -based conductor manufacturing with the same performance of conductors prepared using MgB 2 powders synthesized from commercial B precursor. In particular in previous articles we shown that the laboratory made B has the same critical current density (J c ) performance of milled MgB 2 powders [6][7][8].…”
Section: Introductionmentioning
confidence: 91%
“…The purified B is heat treated at high temperature (1100°C) for 10 h under Ar flow [7] in a furnace directly connected with a glovebox, at the end of the process the powder can be stored under Ar atmosphere or directly used to prepare MgB 2 powder. This precaution avoids the oxidization.…”
Section: Heat Treatment At High Temperaturementioning
confidence: 99%